Characteristic and Development of Cow’s Milk Dadih as an Alternate of Buffalo’s Milk Dadih - Chandra Utami Wirawati (Indonesian Center for Animal Research and Development, 2017)
Dadih is a product of fermented buffalo milk in a bamboo tube from West Sumatera. The decline of buffalo population in West Sumatera caused dadih scarcity. The demand of dadih is high because it is an integral part of the Minangkabau’s diet and culture. Cow milk can be used as a substitute of buffalo milk for producing dadih, although the product has slightly different characteristics, especially lower total solids. Producing cows milk dadih similar to buffalo milk dadih, fresh cow milk should be concentrated and added with skim milk. Single or combination of lactic acid bacteria from the genus Lactobacillus, Lactococcus, Streptococcus and Bifidobacterium from dadih of buffalo milk or commercial culture can be used as a starter. Based on investment analysis, the prospect of developing cows milk dadih is feasible.